Implementasi HACCP Pada Ikan Kerapu Segar (Studi Kasus PT. Bahari Lancar Abadi) - Ni Made Regita Pradnyaswari; Ni Made Darmadi; I Made Kawan (GEMA AGRO, 2024)
The issue of quality and food safety of fishery products is something that cannot be negotiated. It turns out that final product monitoring techniques have not been able to provide quality assurance that food products are free from danger and contamination. Through the implementation of Hazard Analysis Critical Control Point (HACCP) at each stage of the process flow, it is possible to increase operational efficiency, reduce the risk of pollution and prevent hazards through identifying and controlling risk factors. In this regard, PT. Bahari Lancar Abadi, hereinafter referred to as the Fish Processing Unit (UPI), has been carrying out fresh grouper export activities since 2022 with production volumes continuing to increase. The aim of the research is to identify the implementation of HACCP on fresh grouper fish at UPI as a guarantee of the quality and safety of fishery food products so that export activities run effectively and efficiently without any special product rejection in the destination country. For 3 weeks, observations and assessments were carried out regarding the suitability of HACCP implementation in the handling of fresh grouper products throughout the production process. Based on the research results, it is known that UPI implements the HACCP system starting from the basic requirements in the form of implementing good fish processing methods (GMP) and fulfilling the requirements for sanitation standard operating procedures (SSOP) with conditions that meet the requirements based on KP Ministerial Regulation Number 17 of 2019 and implementing 5 (five) steps and 7 (seven) HACCP principles properly in accordance with SNI 01-4852-1998 as a form of consumer protection in the consumption of fishery products through food safety quality control throughout the production process so that export activities run effectively and efficiently without any special product rejection in the destination country.